MAYBE Initial complexity problem: 1: T: (1, 1) f3(a, b) -> f0(1, 1) (?, 1) f0(a, b) -> f0(a + 1, b) start location: f3 leaf cost: 0 Applied AI with 'oct' on problem 1 to obtain the following invariants: For symbol f0: -X_2 + 1 >= 0 /\ X_1 - X_2 >= 0 /\ X_2 - 1 >= 0 /\ X_1 + X_2 - 2 >= 0 /\ X_1 - 1 >= 0 This yielded the following problem: 2: T: (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] (1, 1) f3(a, b) -> f0(1, 1) start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(1, 1) with all transitions in problem 2, the following new transition is obtained: f3(a, b) -> f0(2, 1) [ 0 >= 0 ] We thus obtain the following problem: 3: T: (1, 2) f3(a, b) -> f0(2, 1) [ 0 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(2, 1) [ 0 >= 0 ] with all transitions in problem 3, the following new transition is obtained: f3(a, b) -> f0(3, 1) [ 0 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 4: T: (1, 3) f3(a, b) -> f0(3, 1) [ 0 >= 0 /\ 1 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(3, 1) [ 0 >= 0 /\ 1 >= 0 ] with all transitions in problem 4, the following new transition is obtained: f3(a, b) -> f0(4, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 ] We thus obtain the following problem: 5: T: (1, 4) f3(a, b) -> f0(4, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(4, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 ] with all transitions in problem 5, the following new transition is obtained: f3(a, b) -> f0(5, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 ] We thus obtain the following problem: 6: T: (1, 5) f3(a, b) -> f0(5, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(5, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 ] with all transitions in problem 6, the following new transition is obtained: f3(a, b) -> f0(6, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 ] We thus obtain the following problem: 7: T: (1, 6) f3(a, b) -> f0(6, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(6, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 ] with all transitions in problem 7, the following new transition is obtained: f3(a, b) -> f0(7, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 ] We thus obtain the following problem: 8: T: (1, 7) f3(a, b) -> f0(7, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(7, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 ] with all transitions in problem 8, the following new transition is obtained: f3(a, b) -> f0(8, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 ] We thus obtain the following problem: 9: T: (1, 8) f3(a, b) -> f0(8, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(8, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 ] with all transitions in problem 9, the following new transition is obtained: f3(a, b) -> f0(9, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 ] We thus obtain the following problem: 10: T: (1, 9) f3(a, b) -> f0(9, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(9, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 ] with all transitions in problem 10, the following new transition is obtained: f3(a, b) -> f0(10, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 ] We thus obtain the following problem: 11: T: (1, 10) f3(a, b) -> f0(10, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(10, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 ] with all transitions in problem 11, the following new transition is obtained: f3(a, b) -> f0(11, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 ] We thus obtain the following problem: 12: T: (1, 11) f3(a, b) -> f0(11, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(11, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 ] with all transitions in problem 12, the following new transition is obtained: f3(a, b) -> f0(12, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 /\ 10 >= 0 ] We thus obtain the following problem: 13: T: (1, 12) f3(a, b) -> f0(12, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 /\ 10 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(12, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 /\ 10 >= 0 ] with all transitions in problem 13, the following new transition is obtained: f3(a, b) -> f0(13, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 /\ 10 >= 0 /\ 11 >= 0 ] We thus obtain the following problem: 14: T: (1, 13) f3(a, b) -> f0(13, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 /\ 10 >= 0 /\ 11 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(13, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 /\ 10 >= 0 /\ 11 >= 0 ] with all transitions in problem 14, the following new transition is obtained: f3(a, b) -> f0(14, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 /\ 10 >= 0 /\ 11 >= 0 /\ 12 >= 0 ] We thus obtain the following problem: 15: T: (1, 14) f3(a, b) -> f0(14, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 /\ 10 >= 0 /\ 11 >= 0 /\ 12 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(14, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 /\ 10 >= 0 /\ 11 >= 0 /\ 12 >= 0 ] with all transitions in problem 15, the following new transition is obtained: f3(a, b) -> f0(15, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 /\ 10 >= 0 /\ 11 >= 0 /\ 12 >= 0 /\ 13 >= 0 ] We thus obtain the following problem: 16: T: (1, 15) f3(a, b) -> f0(15, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 /\ 10 >= 0 /\ 11 >= 0 /\ 12 >= 0 /\ 13 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 By chaining the transition f3(a, b) -> f0(15, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 /\ 10 >= 0 /\ 11 >= 0 /\ 12 >= 0 /\ 13 >= 0 ] with all transitions in problem 16, the following new transition is obtained: f3(a, b) -> f0(16, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 /\ 10 >= 0 /\ 11 >= 0 /\ 12 >= 0 /\ 13 >= 0 /\ 14 >= 0 ] We thus obtain the following problem: 17: T: (1, 16) f3(a, b) -> f0(16, 1) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 3 >= 0 /\ 4 >= 0 /\ 5 >= 0 /\ 6 >= 0 /\ 7 >= 0 /\ 8 >= 0 /\ 9 >= 0 /\ 10 >= 0 /\ 11 >= 0 /\ 12 >= 0 /\ 13 >= 0 /\ 14 >= 0 ] (?, 1) f0(a, b) -> f0(a + 1, b) [ -b + 1 >= 0 /\ a - b >= 0 /\ b - 1 >= 0 /\ a + b - 2 >= 0 /\ a - 1 >= 0 ] start location: f3 leaf cost: 0 Complexity upper bound ? Time: 0.625 sec (SMT: 0.577 sec)